FINDING OPTIMAL LOCATION OF DISTRIBUTED GENERATOR BY USING A LOAD FLOW ANALYSIS (International Journal of Food and Nutritional Sciences, 2022)
Distributed Generator when connected to power system, Voltage stability in power system is a major problem that receives international attention. Before connecting Distributed Generator to power system optimal location is necessary to find out. For increase of current and voltage stability as well to achieve power quality, optimal location is must. An open and free source piece of software, Power System Analysis Toolbox (PSAT) is used in this study to create a model of modified IEEE 14 bus system. This paper primarily addressed to find optimal location of distributed generator by using a load flow analysis with the help of MATLAB.